The Features of Frame Interpretation in Translation (On the Material of Ukrainian and Crimeaan Tatar Languages) - Бондаренко, А. (Київський національний університет імені Тараса Шевченка, 2022)
The article reveals the meaning and structure of the concept of "frame" in modern linguistics, as well as outlines the main approaches to the classification of the frame in translation studies as an effective tool to explain the translation process. Later, this classification is used to analyze a number of examples taken from the story of M. Mathios "Armageddon has already taken place", translated by Sh. Sati for the first Ukrainian-Crimean Tatar literary competition "Qmm inciri" ("Crimean Fig"). The special conditions of formation of static and dynamic frames are investigated on examples in the article, and also advantages of use of frame translation for preservation of mental images of the people are shown. The article demonstrates the relevance of frame interpretation of a literary text from Ukrainian into Crimean Tatar as a means of solving problems that arise when translating mental images reflected in the culturally marked vocabulary of the original work into another language in different cultural environment. Finally, the article proves that the frame approach offers a solid theoretical basis for studying and preserving the mental images proposed by the author of the source text and reproduced by the translator, and provides a basis for studying the dynamic process underlying the ability to reproduce information with minimal distortion. Taking into account that frames represent static and dynamic phenomena, I have to admit that it works effectively to describe and explain the translator’s mental process. Translators, in terms of the semantics of frames, can be seen as creators who, operating on frames, seek to achieve cognitive equivalence.

Стаття розкриває зміст і структуру поняття «фрейм» у сучасній лінгвістичній науці, а також окреслює основні піДхоДи До класифікації фрейму у перекладознавстві, як ефективного інструменту Для пояснення процесу перекладу. У нашому науковому доробку ця класифікація застосовується для аналізу художнього твору М. Матіос «Армагедон уже відбувся» у кримськотатарському перекладі Ш. Саті, що було опубліковано у збірнику «Кримський інжир» (2019 року). У статті вперше досліджено особливі умови формування статичного та динамічного фреймів, продемонстровано переваги використання фреймового перекладу задля збереження ментальних образів, задуманих автором, з мінімальним їх викривленням.
Особливості фреймової інтерпретації при перекладі художнього тексту (на матеріалі української та кримськотатарської мов)
Keywords: frame; cognitive unit; interpretation; situational equivalent; dy¬namics; statics.; фрейм; когнітивна одиниця; інтерпретація; ситуати¬вний відповідник; динаміка; статика